Concussions in the National Hockey League: Analysis of Incidence, Return to Play, and Performance. Issue 1 (20th January 2022) - Andrews, Erickson; Jildeh, Toufic R.; Abbas, Muhammad J.; Lindsay-Rivera, Kevin; Berguson, Jon; Okoroha, Kelechi R.
Background: Concussion injuries are common in professional hockey; however, their effect on player performance remains unclear. Purpose: To quantify the effect of concussions on the performance of position players in the National Hockey League (NHL). Study Design: Cohort study; Level of evidence, 3. Methods: Concussion data from the NHL were collected using publicly available databases for the seasons between 2009-2010 and 2015-2016, coinciding with new NHL concussion rules. Age, body mass index, position, number of concussions during a player's NHL career, games played, and time on ice were recorded. Basic and advanced performance metrics were collected for 1 season pre- and postconcussion (short-term period) and 3 seasons before and after concussion (long-term period) to assess short- and long-term changes in performance. A control group of players without an identified concussion who competed during the study period was assembled for comparison. Wilcoxon signed rank tests were used to evaluate pre- to postconcussion data in the short- and long-term settings as well as to compare the cohorts at each time point. Results: Overall, 48 players were identified as having a concussion during the study period. Players missed 17.2 ± 15.1 days (mean ± standard deviation) and 7.5 ± 6.9 games postconcussion. There were no significant differences in any metric when pre- and postconcussion intraseason performance was assessed. Athletes who were concussed demonstrated significantly deceased performance metrics (assists per 60 minutes, points per 60 minutes, Corsi percentage, and Fenwick percentage) in the 3 years after the concussion as compared with the year before injury ( P < .05). However, no difference was found between the concussed group and matched control group in the short- or long-term period. Players with concussion played fewer career games (856.4 ± 287.4 vs 725.7 ± 215.0; P < .05) than did controls. Conclusion: A high rate of NHL players were able to return to play after a concussion injury. Players with concussion did not experience a reduction in performance metrics in the short- or long-term setting when compared with matched controls. The concussed cohort maintained a similar workload up to 3 seasons postconcussion but played in fewer career games when compared with matched controls.